The psychology of human sexuality - Lehmiller, Justin J (John Wiley & Sons Ltd, 2024)
"Sex. Almost everyone does it, but almost no one wants to talk about. It is quite the paradox when you consider how vital sex is to human life. Not only is it the act that propels our species forward, but it can also be a way to bond with a romantic partner, a way to relieve the stress of daily life, not to mention an enjoyable way to pass the time. Of course, sex is not always positive or pleasurable. For some people, sex can be a constant source of anxiety and insecurity or an awkward and embarrassing topic of discussion. Sex can also be a means of exploitation and abuse, not to mention a potential pathway to disease and death. Sex thus has both a light side and a dark side, and each deserves to be acknowledged. The goal of this book is to give you a better understanding of the ins and outs of sex from a psychological perspective. There are many excellent books out there already that tackle this topic from a largely biological or clinical standpoint, and you could certainly learn a lot from reading those texts. However, most of those books give short shrift to the roles that psychology and the social and cultural context play in shaping human sexual behavior. I used many of these books in previous courses I taught and found that students who were majoring in psychology or who took the course because it was advertised as Psychology of Human Sexuality were largely unsatisfied. In fact, the first few times I taught this class, my end-of-semester evaluations looked pretty similar: students commented on how much they loved and enjoyed the course, but wanted to know, "Where's the psychology?" Because I was unable to find a book that truly met the needs and desires of my students, I decided to write this one"-- Provided by publisher.